PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MODEL KOOPERATIF TIPE CONCEPT SENTENCE SISWA KELAS V SD - M. SALEH (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2013)
This research is motivated by the preliminary study , that the Fifth Grade Students of SDN 08 Morning Duri Pulo Central Jakarta Academic Year 2011/2012 low reading ability and difficulty in reading comprehension . low value of Indonesian material test results Writing a simple dialog , it is characterized by the value of students under the KKM . KKM has been determined at 65 , and only a few students achieve mastery KKM . Similarly, teachers in presenting the material still monotonous lectures and students just listen .Research on the use of cooperative learning model concept learning sentence Writing a simple dialogue between two or three characters with attention to the content as well as its role . Based on these problems , the objectives to be achieved are : 1 ) Knowing how the application of cooperative learning model sentence in the material concept of creative writing plays ; 2 ) Knowing implementation concept learning modelkooperatiftipe sentence in creative writing material plays ; 3 ) determine the increase results student learning after using the learning model concept kooperatiftipe sentence . The method used in this research is Classroom Action Research ( CAR), which adapted the model of Kemmis & Mc . Taggart with three cycles, each cycle performed in one action . The results showed improvement in student learning outcomes . In the first cycle of students achieving an average of 41.8 . In the second cycle increased with an average value of 65 and the third cycle the average value reaches 74 or as many as 85 % of students who achieved KKM . Based on the results of this study concluded that the use of cooperative learning model concept sentence type can improve learning outcomes Indonesian